ANALISIS YURIDIS PARATE EKSEKUSI DALAM PASAL 6 UNDANG-UNDANG TENTANG HAK TANGGUNGAN YANG BERTENTANGAN DENGAN PASAL 224 HIR - Siti Rahayu Korompot (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2023)
In carrying out the execution of mortgage rights, if the debtor is negligent or defaults, a warning will be given to the debtor to pay off the debt. However, if the debtor does not respond, direct execution can be carried out on his own power (parate executie) without having to ask for fiat from the Chief Justice and without having to follow the rules of the game in the procedural law. If one looks at the UUHT there is confusion, namely that it is contained in article 6 UUHT with the General Explanation number 9 UUHT and the explanation of Article 14 paragraphs (2) and (3) UUHT which states that the implementation of parate executie is carried out based on Article 224 HIR and Article 258 Rbg. This condition will lead to multiple interpretations. This research will discuss how is the implementation of parate executie mortgage rights based on the provisions in the mortgage rights law? And what are the legal consequences if the parate executie in article 6 of the law on mortgage rights contradicts the provisions of article 224 HIR? This study uses a normative legal approach. The results of this study indicate that parate executie mortgage rights are carried out directly and without fiat from the court, this is different from the general explanation number 9 UUHT which states that parate executie implementation is carried out based on Article 224 HIR and Article 258 Rbg, then based on the asymmetry of these rules causes a conflict of norms between Article 6 UUHT and Article 224 HIR which causes several legal consequences, one of which is the dualism of the judge's opinion in handling parate executie cases.